Service Provider Hesitation in Credence Services: The Importance of Customer Expectations?. Issue 4 (2nd October 2022) - Fuller, Rachel; Pervan, Simon; Kunstler, Breanne; Merolli, Mark
Abstract: This research examines a novel reason for service providers withholding aspects of optimal service quality: hesitation. Previous research has shown that physiotherapists often hold back on delivering non-treatment based physical activity (NTPA) advice over concerns that it is not welcomed by patients. Using a survey method (N = 587), we found that users and non-users of physiotherapy find it likely and important to receive NTPA advice; NTPA is also positively linked to satisfaction. This study debates hesitation as a possible disconnect between customer expectations of value that is co-created in the physiotherapy clinic ("joint sphere") vs. the outside of the clinic ("customer sphere").